Pelindian Fe₂O₃ dari Limbah Karat Besi Menggunakan HCl dan H₂C₂O₄ - Asiyah Nurrahmajanti (Yayasan Literasi Sains Indonesia, 2025)
This study aims to extract iron(III) oxide (Fe₂O₃) from iron rust waste using a leaching method with hydrochloric acid (HCl) and oxalic acid (H₂C₂O₄). After the leaching process with acids, precipitation was carried out using sodium hydroxide (NaOH) solution. The variation in acid type was conducted to evaluate the leaching effectiveness based on the Fe₂O₃ yield obtained. The results showed that HCl was more effective in dissolving Fe₂O₃ compared to H₂C₂O₄. The yields obtained from each acid type were 64.44% for HCl and 24.39% for H₂C₂O₄. The precipitation process was performed at a pH of 5–7 to ensure the formation of a stable Fe(OH)₃ precipitate before being dried into Fe₂O₃. Qualitative analysis using potassium hexacyanoferrate(III) (K₄[Fe(CN)₆]) confirmed the presence of Fe³⁺ ions in the final product from both acid treatments. This method has proven to be effective in obtaining high-quality Fe₂O₃ that can be used in various industrial and research applications. Additionally, this study contributes to the utilization of iron rust waste as a valuable precursor material for direct use or further processing while also reducing environmental pollution.